Jacqueshuberia Ducke (Leguminosae - Caesalpinioideae), um gênero exclusivamente neotropical. - Silva, Marlene Freitas da; Graham, Alan (Acta Amazonica, 1980)
The authors of the present paper have made a taxonomic study of the genus Jacqueshuberia Ducko (Leguminosae-Caesalpinioideae) in South America, including a key for the three species discussed. Some additional notes are also presented on the geographical and ecological distribution of the species, and on the nomenclature of the group.